The Behavior of Hustle Culture among Students in Faculty of Social and Political Science Jenderal Soedirman University - Maharani, Aulia Putri; Martono, Nanang; Rizkidarajat, Wiman (Jayapangus Press, 2024)
Hustle culture is a phenomenon where people usually have work addictions. These past 3 years this phenomenon has become more happening, even it happens among students. The existence of late capitalism and digital portfolios become the main reason that this phenomenon happens among students. The fear of not being successful in the future, the fear of missing out, the feeling of unsatisfied with their education become the prologue of this phenomenon among students. This quantitative research consists of 150 respondents which come from the students of the Faculty of Social and Political Science Jenderal Soedirman University happened because there are so many students in FISIP Unsoed having this behavior. So that, this research aimed to deep dive the reasons also the level of hustling that they have, besides that, this research that is using a survey method to gather the data aimed to know the priority of the students nowadays. This research successfully discovering that most of the students have a moderate hustle culture. It shows that most of the respondents (61.3%) are having a high hustle culture. Most of them (41.30%) said that it happens because of they need a good personal branding also the matter of portfolio. Through this research we also discover that the respondents actually know the importance of their education, however, many aspects of education don’t meet their standards for their future, and it changes their priority, they decided to be a hustling person instead of just being the one that focuses on their education.